Three-Dimensional Poincaré Plot Analysis for Heart Rate Variability. (18th May 2022) - Wang, Bin; Liu, Dewen; Gao, Xin; Luo, Yunlei
Abstract : For the limitation of Poincaré plot analysis, the three-dimensional Poincaré plot analysis is proposed to analyze the heart rate variability. Firstly, the Poincaré plot and some classic indicators are briefly discussed. Because the standard analysis method inherently ignores the embedding temporal information of the RR interval time series, the temporal variation of the time series cannot be adequately reflected. Secondly, for the limitation of the Poincaré plot analysis, a three-dimensional Poincaré plot is presented, which can fully describe the temporal and spatial characteristics of the RR interval time series. Thirdly, we propose the local distribution entropy, which can quantify the temporal and spatial patterns of the scatter points in novel space. Finally, PhysioNet/PhysioBank is applied in this study. The experimental results demonstrate the effectiveness of the three-dimensional Poincaré plot analysis.